Responsiveness of the Malaysian planning system in managing housing supply - Rameli, Alias; Johar, Foziah; Ho, Chin Siong (2006)
The land use planning mechanisms particularly through development plans and development control are recognised as a tool in determining the current and future housing needs, formulation of the housing policies, allocation the amount of land and identification of suitable locations for housing development. The planning mechanisms also play important roles to facilitate and control the housing production process. In relation to the management of housing supply, besides faulty market systems, there is an argument that irresponsiveness of the current planning practice also contributes to the issue of oversupply. The existing planning system which focuses on meeting housing needs, neglects the element of effective demand in housing forecasting. Inefficient development approval process by the Local Planning Authority in `filtering’ and assessing the new housing development application may also contribute to issue of oversupply. Against this background, this paper will highlight the current issues of housing supply in Malaysia and clarify the roles of planning and market system as well as its relationship in the process of housing supply. This paper will also discuss on the nature of the planning system in fulfilling the population requirement for housing and the importance of the market mechanisms in the operation of the housing planning.